The Effectiveness of El-Maksum Mosque Youth Activities in Improving Spiritual Education - Arlina; Arjuna Barkah Firdaus; Dewi Aryanti; Elma Zahara; Jumi Laila Nurzannah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Mosque youth activities are one way to encourage spiritual education. These activities can take the form of recitations, courses, seminars, workshops, religious events and other events aimed at building spiritual education. This research is classified as qualitative research with the type of case study research. This social phenomenon and human problem is the result of researchers' observations while in the field, namely in relation to the effectiveness of mosque youth activities in improving spiritual education. The data collection techniques in this research are observation, interviews and documentation. The results of this research show that there are several activities carried out by teenagers at the El-Massum Mosque in improving spiritual education, including: recital, PHBI activities, joint recitation of 3 villages, dawn safari, joint worship of 3 villages, pious children's festival competition, echo competition drum takbir, and so on. El-Massum mosque youth activities in improving spiritual education have been quite effective. Mosque youth are a benchmark for the sustainability and improvement of a nation, therefore El-Massum mosque youth will continue to support the development of spiritual education for the younger generation.